Effectiveness And Challenges Of Communication Management Of The Tanah Bumbu General Election Commission In The Socialization Of The Candidacy Stage Of The 2024 Regional Head Election - Mubarok, Bustanul; Swarnawati, Aminah (UNIVERSITAS PAKUAN, 2025)
The regional head election (Pilkada) is a contestation that requires proper management. One of the most important management aspects is the Communication Management by the General Election Commission (KPU) as the organizer of the regional head election. KPU Tanah Bumbu, as the organizer of the Pilkada in Tanah Bumbu Regency, South Kalimantan, has implemented communication management adjusted to various problems and the dynamics of local politics. The purpose of this study is to assess the effectiveness and challenges of communication management by the General Election Commission (KPU) of Tanah Bumbu Regency during the candidacy stage in the implementation of the 2024 Regional Head Election (Pilkada). This research was conducted in Tanah Bumbu Regency during the candidacy stage of the Pilkada 2024 participants. The research method used is descriptive qualitative with a case study approach. Data collection techniques employed in this study included in-depth interviews, observation, and documentation. The study found that the communication management strategy of KPU Tanah Bumbu relies on communicators’ competence resources which are already good, adequate technological support, well-established cooperative relationships with related parties, and the availability of very sufficient budget. This study also successfully identified the main challenges of communication management faced by KPU Tanah Bumbu, namely the low level of public literacy, infrastructural obstacles, and unpredictable socio-political dynamics.